Back to Basics: An Example Application of a Biopsychosocial Assessment - Greeno, Elizabeth J. (International Journal of Psychosocial Rehabilitation, 2014)
A first step in treating women with substance use disorders during pregnancy is the completion of a comprehensive psychosocial assessment, such as the Mega Interactive Model of Substance Use Among Women (MIMSUAW). This study is guided by the MIMSUAW, a biopsychosocial framework (Pagliaro & Pagliaro, 1996, 2000). Findings from the MIMSUAW indicate baseline functioning and can be applied to treatment planning. This study supports the use of structured psychosocial assessment by social workers.